Expression and production of the long pentraxin PTX3 in rheumatoid arthritis (RA) - Luchetti, M. M.; Piccinini, G.; Mantovani, A.; Peri, G.; Matteucci, C.; Pomponio, G.; Fratini, M.; Fraticelli, P.; Sambo, P.; Di Loreto, C.; Doni, A.; Introna, M.; et al. (Clinical and experimental immunology, 2000)
PTX3 is a secreted molecule which consists of a C‐terminal domain similar to classical pentraxins (e.g. C‐reactive protein (CRP)) and of an unrelated N‐terminal domain. Unlike the classical pentraxins, the long pentraxin PTX3 is expressed in response to IL‐1β and tumour necrosis factor‐alpha (TNF‐α), but not to IL‐6, in various cell types. The present study was designed to investigate the expression of PTX3 in RA. Dissociated RA and osteoarthritis (OA) type B synoviocytes were cultured in the presence and in the absence of inflammatory cytokines. PTX3 mRNA expression in synoviocytes was evaluated by Northern analysis. PTX3 protein levels in synovial cell cultures and synovial fluid were estimated by ELISA, and PTX3 distribution in synovial tissues by immunohistochemical techniques. OA synoviocytes were induced to express high levels of PTX3 mRNA by TNF‐α, but not by other cytokines including IL‐1β and IL‐6. RA synoviocytes, unlike OA synoviocytes, constitutively expressed high levels of PTX3 in the absence of deliberate stimulation. The constitutive expression of PTX3 in RA synoviocytes was not modified by anti‐TNF‐α antibodies, IL‐1 receptor antagonist or a combination of the two agents. In contrast, interferon‐gamma and transforming growth factor‐beta inhibited PTX3 constitutive expression in RA synoviocytes. The joint fluid from RA patients contained higher levels of immunoreactive PTX3 than controls and the synovial tissue contained endothelial cells and synoviocytes positive for PTX3 by immunohistochemistry. In conclusion, PTX3 may play a role in inflammatory circuits of RA, and its relevance as a marker of disease activity deserves further study.